Polarization Routers: Nanophotonic Polarization Routers Based on an Intelligent Algorithm (Advanced Optical Materials 10/2020). Issue 10 (18th May 2020) - Lu, Cuicui; Liu, Zhouhui; Wu, You; Xiao, Zhiyuan; Yu, Dongyi; Zhang, Hongyu; Wang, Chenyang; Hu, Xiaoyong; Liu, Yong‐Chun; Liu, Xiaohong; Zhang, Xiangdong
Abstract : A polarization router can separate and steer light with different polarizations into different output ports. In article number 1902018, Cuicui Lu, Xiaoyong Hu and co‐workers realize on‐chip polarization routers based on an intelligent algorithm constructed by genetic algorithm and finite element method. A silicon‐based polarization router with footprint of only 970 nm × 1240 nm is realized, which is the smallest one ever demonstrated experimentally. Meanwhile, various polarization routers possessing different operation bands, structures and materials are designed by this intelligent algorithm. This work provides a scheme for high‐density on‐chip integration of nanophotonic devices.